Effect of different storage conditions on guggulsterone content in oleo-gum resin of Commiphora wightii - Suman Singh,; N Manika,; Ram K Verma,; Guru Das Bagchi, (International Journal of Phytomedicine, 2013)
Effects of light, temperature, packaging and duration of storage was investigated on the active constituents of Commiphora wightii oleo-gum resin. The freshly collected oleo-gum resins were packed in borosilicate Glass (GL), polypropylene (PP) and polystyrene (PS) vials, and were stored at 10ºC, 20 ºC, 30 ºC and 40ºC respectively for eight months in dark and at 20ºC, and 30ºC in light. Total guggulsterone (GS), guggulsterone-E (GSE) and guggulsterone-Z (GSZ) content was estimated in the oleo-gum resin every month for eight months with the help of HPLC. Study showed that GS, and GSZ are very sensitive to high temperature (>40 ºC) and light and deteriorate very quickly. While, GSE content showed an increase at this temperature. Among the studied vials, air tight dark colored GL vials were observed to retain total GS and GSZ content for longer period. Since, total GS / GSZ are mainly responsible for medicinal properties of ‘Guggul’ oleo-gum resin; therefore, for better efficacy of the drug, it should be kept at low temperature (10 ºC) in dark air tight Glass containers. At this condition, the oleo-gum resin shows only 16.04% loss in total GS and 9.23% loss in GSZ content after six months of storage. The study has demonstrated proper commercial storage conditions of the drug for longer use without losing its efficacy.